The Effects of China's Sloping Land Conversion Program on Agricultural Households - Zhen Liu; Arne Henningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
In the late 1990s, China aimed to mitigate environmental degradation from agricultural production activities by introducing the world's largest 'Payments for Environmental Services' (PES) program 1em1pt the Sloping Land Conversion Program (SLCP). In order to analyze its effects on agricultural households, we develop a microeconomic Agricultural Household Model (AHM), which can model the production, consumption, and non-farm labor supply decisions of agricultural households in rural China in a theoretically consistent fashion. Based on this theoretical model, we derive an empirical specification that we use to econometrically estimate the effects of the SLCP and other exogenous factors. Using a large longitudinal farm household survey data set, we estimate the empirical model with the Hausman-Taylor estimation method. The empirical results are generally consistent with the results of our theoretical comparative static analysis, e.g. that the SLCP significantly decreases agricultural production. While the SLCP increases non-farm labor supply and total consumption in the Yellow River basin, these effects could not be observed in the Yangtze River basin. The recent reduction of the SLCP compensation payment rates has had some notable, but generally small effects.
Keywords: H31; Q12; R38; 330; Sloping Land Conversion Program; Agricultural household model; Household behavior; Hausman-Taylor Estimator; China